Australian practice nursing: collaboration in context. Issue 23 (2nd May 2014) - Merrick, Eamon; Fry, Margaret; Duffield, Christine
<x xml:space="preserve">Abstract</x> Aims and objectives To explore whether or not the context of Australian practice nursing supports collaborative decision‐making about organisation and delivery of patient care. Background Positive patient outcomes depend on Australian practice nurses participating in collaborative and interprofessional services, particularly for patients with chronic disease(s). It is unclear whether Australian practice nurses have the opportunity to collaborate in decision‐making or how traditional organisational structures may support or hinder collaboration. Design This is a descriptive exploratory study. Semi‐structured interviews were conducted using a purposive sample of practice nurses (n = 15). Thematic analysis was used to provide meaningful and contextual insights into how practice nurses participate in decision‐making. Method An interview tool, based on available literature, was developed and consisted of thirty open‐ended questions to direct discussion during telephone interviews. Transcribed data were imported into NVivotm for analysis and interpretation. The collection, analysis and thematic interpretation of data were an iterative process. Findings Participants fostered trusting interprofessional relationships, which enabled them to influence medical decision‐making and thereby advocate for patient need. Trusting interprofessional relationships were perceived to alter the relative roles of the medical practitioner and practice nurse and enhance the opportunities for collaborative decision‐making. Conclusions and relevance to clinical practice Collaborative interprofessional care in Australian general practice must occur if increased demands for care are to be met. It is timely to consider how government policy, financial regulations and the organisation of Australian general practice can better support and enhance a collaborative contribution to care by practice nurses.